(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2018)
This study was aimed to compare the peri-operative outcomes among the mitral valve replace-ment using anterolateral thoracotomy (n=17) and standard median sternotomy (n=17) in a single surgeons practice. The mean age was 24.1 ± 5.3 years in Group I and 41.0 ± 11.5 years in Group II. Female was predominant in Group I. Total operative time and bypass time were significant in both the study groups. Incision scar was not visible in females in Group I but full incision scar was visible in Group II in sitting posture. In Group I patients, majority (52.9%) patients needed short duration of ICU stay in comparison to Group II, and the difference was statistically significant (p<0.05) between the two groups. During discharge, 94.1% wound was well healed in Group I and 70.6% in Group II. Wound dehiscence was nil in Group I, but 23.5% patients developed dehiscence in Group II. However, only 5.9% patient developed unstable sternum in Group II. Cosmetic mitral valve replacement can be done safely through anterolateral thoracotomy and it is cost effective especially for the developing countries.